Debugging C++ troubleshooting for programmers - Pappas, Chris H. 1953- (Osborne/McGraw-Hill, 2000)
-- Troubleshooting reference for the C++ programmer.-- Stands alone and can be paired with other Debugging titles covering Java, ASP, and other technologies.-- Filled with solutions to common and fare bugs